2021
DOI: 10.37939/jrmc.v25i4.1703
|View full text |Cite
|
Sign up to set email alerts
|

Kinesiophobia and its association with balance and mobility in knee osteoarthritis patients in Rawalpindi & Islamabad

Abstract: Objective: The purpose of this study was to evaluate the relationship of fear avoidance belief or kinesiophobia with balance and mobility in knee osteoarthritis patients. Materials and methods: This cross-sectional correlational study was conducted in Fauji Foundation Hospital, Benazir Bhutto Hospital and Holy Family Hospital, Rawalpindi/Islamabad from January 2019 to June 2019. A total of 64 knee osteoarthritis patients (both male and female) between the ages of 40- 60 years were included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…A survey by Global Burden of Disease on knee osteoarthritis showed that 3.8% suffered globally knee OA in which the highest ratio was found in Asia Pacific high income countries while this ratio was gradually decreased in United states and South Asia respectively 3 . Study conducted in Twin cities identified the association of knee OA with poor quality of life and history of fall 4 .…”
Section: Introductionmentioning
confidence: 99%
“…A survey by Global Burden of Disease on knee osteoarthritis showed that 3.8% suffered globally knee OA in which the highest ratio was found in Asia Pacific high income countries while this ratio was gradually decreased in United states and South Asia respectively 3 . Study conducted in Twin cities identified the association of knee OA with poor quality of life and history of fall 4 .…”
Section: Introductionmentioning
confidence: 99%